Analisis Risiko Unit Value Komoditas Ekspor Kelapa di Kalimantan Barat: Risk Analysis of Unit Value of Coconut Export Commodities in West Kalimantan - Maresha Widya Muliadiasti; Supandi Supandi; Evy Sulistianingsih (Badan Pusat Statistik Provinsi Kalimantan Barat, 2024)
Coconut is one of the leading commodities in West Kalimantan that can produce throughout the year. Coconut is also one of the largest contributors to Regional Original Income (PAD) in West Kalimantan. Coconut export commodities and other processed products have increased exports to European Union countries. The unit value index is used to calculate the trade exchange rate by comparing the development of the export unit value index with the import unit value index. The unit value of each coconut commodity can be calculated by dividing the export value (US) by the export volume (Kg) in each month. Value at Risk (VaR) is used to estimate the maximum loss experienced by investors in the capital market at a certain level of confidence. This study uses the VaR concept with the Cornish-Fisher method to estimate the losses of coconut exporters. Based on the results of the analysis, it can be concluded that with a 95% confidence level, coconut exporters in West Kalimantan Province will experience a loss of 362,602.9 US/Kg if exporters export coconuts at 1,000,000 US/Kg.